Overview of the oxygen isotope systematics of land snails from North America. Issue 1 (3rd October 2018) - Yanes, Yurena; Al-Qattan, Nasser M.; Rech, Jason A.; Pigati, Jeffrey S.; Dodd, Justin P.; Nekola, Jeffrey C.
Abstract: Continental paleoclimate proxies with near-global coverage are rare. Land snail δ 18 O is one of the few proxies abundant in Quaternary sediments ranging from the tropics to the high Arctic tundra. However, its application in paleoclimatology remains difficult, attributable in part to limitations in published calibration studies. Here we present shell δ 18 O of modern small (<10 mm) snails across North America, from Florida (30°N) to Manitoba (58°N), to examine the main climatic controls on shell δ 18 O at a coarse scale. This transect is augmented by published δ 18 O values, which expand our coverage from Jamaica (18°N) to Alaska (64°N). Results indicate that shell δ 18 O primarily tracks the average annual precipitation δ 18 O. Shell δ 18 O increases 0.5–0.7‰ for every 1‰ increase in precipitation δ 18 O, and 0.3–0.7‰ for every 1°C increase in temperature. These relationships hold true when all taxa are included regardless of body size (ranging from 1.6 to 58 mm), ecology (herbivores, omnivores, and carnivores), or behavior (variable seasonal active periods and mobility habits). Future isotopic investigations should include calibration studies in tropical and high-latitude settings, arid environments, and along altitudinal gradients to test if the near linear relationship between shell and meteoric precipitation δ 18 O observed on a continental scale remains significant.